A Companion to American art - Davis, John 1961 September 24-; Greenhill, Jennifer A. 1974-; LaFountain, Jason David (Chichester, West Sussex, United Kingdom Wiley Blackwell, 2015)
A companion to American art presents 35 newly-commissioned essays by leading scholars that explore themethodology, historiography, and current state of the field of American art history.
Part I Writing American art history -- Part II Geographies : rethinking Americanness -- Part III Subjectivities -- Part IV Art and public culture.
Includes bibliographical references and index.
Keywords: Art, American